Economic and Social Panorama of the Community of Latin American and Caribbean States, 2016 - NU. CEPAL (ECLAC, 2017)
This edition of the Economic and Social Panorama of the Community of Latin American and Caribbean States is a contribution by the Economic Commission for Latin America and the Caribbean (ECLAC) to the fifth Summit of Heads of State and Government of the Community of Latin American and Caribbean States (CELAC),(Punta Cana, Dominican Republic, January 2017). The document has six sections summarizing the situation in Latin America and the Caribbean as regards economic, social and population affairs, as well as foreign direct investment, trade and gender equality.